2016
DOI: 10.1039/c5ob02296g
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial diterpenoid dimers of a new carbon skeleton from Aphanamixis grandifolia

Abstract: Chemical investigation into the minor constituents of Aphanamixis grandifolia yielded three new diterpenoid dimers, aphadilactones E-G (1-3) featuring a new carbon skeleton. Their structures and absolute configurations were fully established by comprehensive spectroscopic data analysis and ECD calculation. Discovery of another two new dimers (4 and 5) suggested the structure of recently reported aphanamene A to be re-investigated. Compounds 1-5 showed moderate antimalarial activities with low micromolar IC50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Chiral HPLC dramatically accelerated the isolation of stereoisomers, especially those with complex structures like diterpenoid dimers [7][8][9]. In recent years, ECD calculations have been widely used to determine the absolute configurations of diterpenoid dimers [7,[9][10][11]. According to our literature review, around 31 publications related to diterpenoid dimers were found before 2000, and this number has increased to 88 in January 2016.…”
Section: Dgatmentioning
confidence: 99%
See 3 more Smart Citations
“…Chiral HPLC dramatically accelerated the isolation of stereoisomers, especially those with complex structures like diterpenoid dimers [7][8][9]. In recent years, ECD calculations have been widely used to determine the absolute configurations of diterpenoid dimers [7,[9][10][11]. According to our literature review, around 31 publications related to diterpenoid dimers were found before 2000, and this number has increased to 88 in January 2016.…”
Section: Dgatmentioning
confidence: 99%
“…Furthermore, the development of purification and structural elucidation methods, especially preparative HPLC and high resolution NMR, makes it now possible to identify compounds at trace amounts. Chiral HPLC dramatically accelerated the isolation of stereoisomers, especially those with complex structures like diterpenoid dimers [7][8][9]. In recent years, ECD calculations have been widely used to determine the absolute configurations of diterpenoid dimers [7,[9][10][11].…”
Section: Dgatmentioning
confidence: 99%
See 2 more Smart Citations
“…Annotinolides A–C ( 671 - 673 ), three novel 7,8-seco-lycopodanoid 8,5-lactones, were afforded by Lycopodium annotinum (Tang et al, 2016b ). Aphanamixis grandifolia (Hainan, China) produced three novel diterpenoids dimers, aphadilactones E–G ( 674 - 676 ) (Zhang et al, 2016b ). Artaboterpenoid A ( 677 ) and (±)-artaboterpenoid B ((±)- 678 ), two new bisabolene-derived sesquiterpenoids, were obtained from the roots of Artabotrys hexapetalus (Xi et al, 2016 ).…”
Section: Terrestrial Plantsmentioning
confidence: 99%